Zap70 inhibits Syk‐mediated osteoclast function1. Issue 8 (12th June 2013) - Zou, Wei; Croke, Monica; Fukunaga, Tomohiro; Broekelmann, Thomas J.; Mecham, Robert P.; Teitelbaum, Steven L.
Abstract The αvβ3 integrin stimulates the resorptive capacity of the differentiated osteoclast (OC) by organizing its cytoskeleton via the tyrosine kinase, Syk. Thus, Syk‐deficient OCs fails to spread or form actin rings, in vitro and in vivo. The Syk family of tyrosine kinases consists of Syk itself and Zap70 which are expressed by different cell types. Because of their structural similarity, and its compensatory properties in other cells, we asked if Zap70 can substitute for absence of Syk in OCs. While expression of Syk, as expected, normalizes the cytoskeletal abnormalities of Syk−/− OCs, Zap70 fails do so. In keeping with this observation, Syk, but not Zap70, rescues αvβ3 integrin‐induced SLP76 phosphorylation in Syk−/− OCs. Furthermore the kinase sequence of Syk partially rescues the Syk−/− phenotype but full normalization also requires its SH2 domains. Surprisingly, expression of Zap70 inhibits WT OC spreading, actin ring formation and bone resorptive activity, but not differentiation. In keeping with arrested cytoskeletal organization, Zap70 blocks integrin‐activated endogenous Syk and Vav3, SLP76 phosphorylation. Such inhibition requires Zap70 kinase activity, as it is abolished by mutation of the Zap70 kinase domain. Thus, while the kinase domain of Syk is uniquely required for OC function that of Zap70 inhibits it. J. Cell. Biochem. 114: 1871–1878, 2013. © 2013 Wiley Periodicals, Inc.